2014
DOI: 10.5539/jfr.v4n2p16
|View full text |Cite
|
Sign up to set email alerts
|

Having Enough Cultural Food? A Qualitative Exploration of the Experiences of Migrants in a Regional Area of Australia

Abstract: The notion of food security encompasses the ability of individuals, households and communities to acquire food that is healthy, sustainable, affordable, appropriate and accessible. Despite Australia's current ability to produce more food than required for its population, there has been substantial evidence demonstrating that many Australians struggle to feed themselves, particularly those from a cultural and linguistically diverse (CALD) background. This qualitative phenomenological study investigated the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(34 citation statements)
references
References 15 publications
2
32
0
Order By: Relevance
“…Immigrants reported that there was an overall abundance of food in the host country (64,70,86) ; produce was always available and not just seasonally as they were used to (71,83,88,91) . Eating a healthy diet based on fresh foods was challenging as they were more difficult to access, particularly in smaller metropolitan areas that depended on seasonal produce (69) while neighbourhoods were filled with stores providing unhealthy options (41,61) .…”
Section: Availability Of Specific Food Typesmentioning
confidence: 99%
See 4 more Smart Citations
“…Immigrants reported that there was an overall abundance of food in the host country (64,70,86) ; produce was always available and not just seasonally as they were used to (71,83,88,91) . Eating a healthy diet based on fresh foods was challenging as they were more difficult to access, particularly in smaller metropolitan areas that depended on seasonal produce (69) while neighbourhoods were filled with stores providing unhealthy options (41,61) .…”
Section: Availability Of Specific Food Typesmentioning
confidence: 99%
“…Moreover, the articles referred to an increased availability of cultural including halal foods over time (2,85,86,91) . In different settings, some groups had an easier time than others to find their cultural foods, though many found it a challenge (58,61,62,68,70,73,75,76,82,86,91) . There was a lack of familiarity and variety thereof (86) .…”
Section: Availability Of Specific Food Typesmentioning
confidence: 99%
See 3 more Smart Citations